A perovskite thin film gas phase passivation method and a perovskite solar cell and a preparation method thereof

CN122935104APending Publication Date: 2026-10-16UNIV OF SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510439316.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]本发明的目的是克服现有钙钛矿薄膜的表面钝化方法无法适应绒面晶硅-钙钛矿叠层太阳能电池的钝化,且钙钛矿薄膜表面钝化效果有待提升的缺陷和不足,提供一种钙钛矿薄膜气相钝化方法,

Benefits of technology

[0045]本发明的钙钛矿薄膜气相钝化方法在不引入溶剂的前提下精准控制钝化层的厚度,适用于大面积钙钛矿电池组件和绒面晶硅-钙钛矿叠层电池的钝化,进一步满足工业化生产的需要。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122935104A_ABST
    Figure CN122935104A_ABST
Patent Text Reader

Abstract

The application discloses a perovskite thin film gas-phase passivation method and a perovskite solar cell and a preparation method thereof, and relates to the technical field of solar cells. The perovskite thin film gas-phase passivation method comprises the following steps: forming a perovskite-passivation agent intermediate on the surface of a perovskite thin film by vacuum evaporation, and forming a passivation layer after annealing the perovskite thin film intermediate, so as to obtain a passivated perovskite thin film. The perovskite thin film gas-phase passivation method can precisely control the thickness of the passivation layer without introducing a solvent, is suitable for the passivation of large-area perovskite battery components and textured crystalline silicon-perovskite laminated batteries, and further promotes crystallization and passivation defects through annealing operation of the perovskite thin film intermediate, so that effective passivation of perovskite thin film defects is realized, the open-circuit voltage and the fill factor of the perovskite solar cell are improved, and thus the battery efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solar cell technology, and more specifically, to a perovskite thin film vapor phase passivation method and a perovskite solar cell and its fabrication method. Background Technology

[0002] Perovskite solar cells are a novel solar cell technology that has attracted widespread attention due to their low cost and high efficiency, reaching 26.7%. However, perovskite solar cells suffer from numerous harmful defects, such as interstitial gaps, vacancies, and impurities within the perovskite structure, as well as grain boundary and interface defects caused by dangling bonds on grain boundaries and crystal surfaces during perovskite film formation. These defects severely affect carrier transport and hinder further improvements in energy conversion efficiency. Therefore, passivating harmful defects in perovskite films is crucial for improving the efficiency and stability of perovskite solar cells. Currently, most reported methods for passivating perovskite solar cells with high efficiency are based on solution spin coating. Solution-based passivation methods often suffer from solvent penetration and contact, damaging the surface or internal structure of the perovskite and causing additional defects, thus affecting efficiency and stability. Furthermore, spin coating is unsuitable for large-area production. During the application of large-area passivating agent solutions, issues such as solution evaporation and turbulence arise, leading to uneven distribution of the passivating agent on the perovskite surface and the potential for salt accumulation in some areas, reducing the yield of large-area perovskite solar cells. Furthermore, the solution spin-coating passivating agent method has certain requirements on the roughness of the bottom interface, and it cannot achieve a uniform and conformal passivation coating on the textured surface. This is obviously detrimental to the passivation and efficiency improvement of textured silicon-perovskite tandem solar cells. Therefore, there is an urgent need for a solvent-free perovskite thin film passivation method that meets the requirements of large-area processes and conformal passivation, further adapting to the process production needs of large-area perovskite solar cells and silicon-perovskite tandem solar cells.

[0003] Existing technology discloses a surface passivation method for perovskite thin films and its application, which achieves surface passivation of perovskite thin films by preparing a PMAI layer on the surface of the perovskite thin film using single-source vapor deposition. However, this method does not solve the problem of passivation adaptability to textured silicon-perovskite tandem solar cells, and the passivation effect needs further improvement. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings and deficiencies of existing perovskite thin film surface passivation methods, which cannot adapt to the passivation of textured silicon-perovskite tandem solar cells and whose perovskite thin film surface passivation effect needs to be improved, and to provide a perovskite thin film vapor phase passivation method.

[0005] Another object of the present invention is to provide a perovskite solar cell.

[0006] Another object of the present invention is to provide a method for preparing a perovskite solar cell.

[0007] The above-mentioned objective of this invention is achieved through the following technical solution:

[0008] A method for vapor-phase passivation of perovskite thin films includes the following steps:

[0009] A perovskite-passivating agent intermediate is formed on the surface of a perovskite film by vacuum evaporation. The perovskite film intermediate is then annealed to form a passivation layer, resulting in a passivated perovskite film.

[0010] The annealing temperature is 80℃~120℃, the humidity is 20%~60%, and the annealing time is 1~10 minutes.

[0011] It should be noted that:

[0012] This invention employs vacuum evaporation to form a perovskite-passivating agent intermediate on the surface of a perovskite thin film. The following method can be used as a reference:

[0013] The perovskite film to be passivated is placed in a vacuum chamber, an evaporation boat is placed below the perovskite film, a passivating agent is added to the evaporation boat, and then heated to evaporate the passivating agent, thereby forming a passivating agent layer on the surface of the perovskite film.

[0014] The perovskite thin film composition of the present invention is ABX3, wherein A is MA. + FA + Cs + One or more of the following, where B is Pb 2+ Sn 2+ One or more, where X is Cl - ,Br - I - One or more of the following.

[0015] This invention uses vacuum evaporation to passivate surface defects in perovskite thin films. It can precisely control the thickness of the passivation layer without introducing solvents, making it suitable for passivation of large-area perovskite solar cell modules and textured silicon-perovskite tandem solar cells, further meeting the needs of industrial production.

[0016] In the perovskite thin film vapor-phase passivation method of this invention, the annealing step is also necessary and important. Annealing can further increase the crystallinity of the perovskite thin film and enhance the passivation effect. After annealing, the vacuum evaporation thickness will be further reduced. If the evaporation thickness is too thick, the performance will decrease, resulting in low photoelectric conversion efficiency, low open-circuit voltage, and a decrease in fill factor. In the annealing operation of this invention, the control of annealing temperature and humidity further promotes crystallization and passivates defects, achieving a better perovskite thin film surface passivation effect, thereby resulting in better photoelectric conversion efficiency in perovskite solar cells, and a significant increase in open-circuit voltage and fill factor. If the annealing temperature and humidity are too low, the reaction cannot be fully achieved to achieve the annealing effect; if the annealing temperature and humidity are too high, it will lead to damage to the perovskite thin film, also failing to achieve the passivation effect, resulting in insignificant improvement in device efficiency, or even a decrease.

[0017] This invention treats the surface of perovskite thin films by vapor-phase vacuum evaporation of passivating agents, achieving effective passivation of defects in the perovskite thin films. This passivation reduces non-radiative recombination losses, suppresses interfacial recombination, and improves the open-circuit voltage and fill factor of perovskite solar cells, thereby enhancing cell efficiency.

[0018] In addition, the passivation process significantly improves the battery's operational stability, thermal stability, and reverse bias stability, which is beneficial for the long-term stable operation of the battery.

[0019] In some specific embodiments, the present invention preferably uses an annealing temperature of 100°C, a humidity of 30% to 40%, and an annealing time of 5 minutes.

[0020] In some specific embodiments, in order to achieve a better passivation effect, preferably, the thickness of the perovskite-passivating agent intermediate is 0.1-20 nm, more preferably 3-10 nm, and even more preferably 5 nm.

[0021] In some specific embodiments, preferably, the vacuum evaporation rate is: The gas pressure inside the chamber during vapor deposition is 1*10 -2 ~1*10 -4 Pa.

[0022] In specific embodiments, the passivating agent of the present invention is a conventional gas-phase passivating agent in the art, such as a small molecule organic halide salt AX.

[0023] Among them, A in the small molecule organic halide salt AX + X is any one of the following: methylamine, ethylamine, propylamine, pentylamine, benzylamine, and phenethylamine ion. -It is any one or more of the following: chloride ion, bromide ion, iodide ion, cyanate ion, thiocyanate ion, trifluoroacetate ion, hexafluorophosphate ion, methanesulfonate ion, tetrafluoroborate ion, acetate ion, and formate ion.

[0024] In this invention, a small-molecule ammonium salt is used as the passivating agent. Small-molecule ammonium salts can promote preferential grain growth to a larger grain size, thereby reducing grain boundary density. Due to their zwitterionic properties, they can passivate surface ionic defects in perovskites. This passivation helps reduce non-radiative recombination on the perovskite surface, thereby improving the photoelectric conversion efficiency of the battery. Furthermore, the interaction between the small-molecule ammonium salt and the perovskite surface can form an interfacial dipole, which helps induce vacuum level bending, thereby improving the bandgap matching of the interface.

[0025] This invention also specifically protects a solar cell, comprising, in sequence, a substrate, a hole transport layer, a passivated perovskite thin film layer, an electron transport layer, a hole blocking layer, and an electrode, wherein the passivated perovskite thin film layer is prepared by the perovskite thin film vapor phase passivation method.

[0026] The passivated perovskite thin film layer prepared by the perovskite thin film vapor phase passivation method of the present invention has good performance in both inverted (pin) and normal (nip) perovskite solar cells.

[0027] The perovskite thin film vapor phase passivation method of the present invention is not only applicable to small-area single-junction cells, but also applicable to large-area module cells and textured silicon-perovskite tandem cells. It can achieve uniform and conformal passivation on perovskites of different sizes and perovskites on different substrates, and the passivation layer thickness can be conveniently and flexibly adjusted as needed.

[0028] The perovskite thin film vapor-phase passivation method used in this invention is applicable to perovskite single-junction, large-area modules, multi-junction stacked, crystalline silicon-perovskite stacked (planar, textured, rough) solar cells, photodetectors, LEDs, and other optoelectronic devices. Furthermore, it is suitable for flexible devices due to its advantages such as solvent-free operation, low-temperature processing, and conformal coating.

[0029] The solar cells of the present invention include various solar cells in the art, such as any one of textured silicon-perovskite tandem solar cells, large-area perovskite solar cells, and small-area single-junction perovskite solar cells.

[0030] The solar cells of the present invention particularly include large-area perovskite solar cells, which solve the problems of solution evaporation and turbulence in the preparation of large-area perovskite solar cells by spin coating process, and can form uniform passivation on the perovskite surface, which greatly improves the yield of large-area perovskite solar cells.

[0031] The solar cells of the present invention also particularly include textured silicon-perovskite tandem solar cells, which have wide adaptability to the roughness of the bottom interface and can achieve a uniform and conformal passivation coating on the textured surface, which is beneficial to improving the efficiency of textured silicon-perovskite tandem solar cells.

[0032] This invention also specifically protects a method for preparing a perovskite solar cell, comprising the following steps:

[0033] S1. Prepare a hole transport layer on a substrate;

[0034] S2. Prepare a perovskite thin film on the hole transport layer obtained in step S1;

[0035] S3. A passivated perovskite thin film layer is prepared by the perovskite thin film vapor phase passivation method of the present invention;

[0036] S4. An electron transport layer is prepared on the layer obtained in step S3;

[0037] S5. A hole-blocking layer is prepared on the layer obtained in step S4.

[0038] S6. Prepare a back electrode on the layer obtained in step S5.

[0039] It should be noted that:

[0040] The substrate of this invention can be ITO, FTO, or textured silicon substrate, etc.

[0041] In specific embodiments, the perovskite thin film of the present invention can be prepared by any feasible method in the art, such as by one or a combination of methods selected from solution spin coating, solution blade coating, solution slot coating, solution spraying, solution inkjet printing, vacuum evaporation, laser ablation, and magnetron sputtering.

[0042] In the above-mentioned junction solar cell structure of the present invention, the P-type transport layer can be one or more of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), nickel oxide (NiOx), self-assembled phosphate molecules (2PACz, Me-4PACz, MeO-2PACz), poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), and 4-butyl-N,N-diphenylaniline homopolymer (Ploy-TPD), but is not limited to the transport layer materials listed above.

[0043] The N-type electron transport layer can be made of fullerene (C 60 C 70 Transport layer materials, including but not limited to the transport layer materials listed above, such as PCBM, ICBA, tin oxide (SnO2), and titanium oxide (TiO2).

[0044] Compared with the prior art, the beneficial effects of the present invention are:

[0045] The perovskite thin film vapor phase passivation method of the present invention can precisely control the thickness of the passivation layer without introducing solvents, and is suitable for passivation of large-area perovskite battery modules and textured silicon-perovskite tandem batteries, further meeting the needs of industrial production.

[0046] Furthermore, the perovskite thin film vapor phase passivation method of the present invention further promotes crystallization and passivates defects through the annealing operation of the perovskite thin film intermediate, thereby achieving effective passivation of perovskite thin film defects. This passivation reduces non-radiative recombination loss, suppresses interfacial recombination, and improves the open-circuit voltage and fill factor of perovskite solar cells, thereby improving cell efficiency. Attached Figure Description

[0047] Figure 1 This is a schematic diagram of a single-junction pin solar cell structure with vacuum evaporation vapor phase passivation according to the present invention.

[0048] Figure 2 This is a schematic diagram of vacuum vapor deposition passivation according to the present invention.

[0049] Figure 3 This is a schematic diagram of a perovskite solar cell module structure with vacuum evaporation vapor phase passivation according to the present invention.

[0050] Figure 4 This is a schematic diagram of a crystalline silicon-perovskite tandem solar cell structure with vacuum evaporation vapor phase passivation according to the present invention.

[0051] Figure 5 The current density-voltage curves of the single-junction pin cells in Example 1 and Comparative Example 1 of this invention are shown.

[0052] Figure 6 The current density-voltage curves of the component cells in Example 2 and Comparative Examples 2 and 3 of the present invention are shown.

[0053] Figure 7 The current density-voltage curves of the stacked batteries in Example 3 and Comparative Examples 4 and 5 of this invention are shown.

[0054] Figure 8 This is a scanning electron microscope image of the stacked battery in Embodiment 3 of the present invention.

[0055] Figure 9 This is a scanning electron microscope image of the stacked battery of Comparative Example 4 of the present invention.

[0056] Figure 10 The X-ray diffraction patterns are those of Example 1 and Comparative Examples 1 and 6 of the present invention.

[0057] Figure 11 The current density-voltage curves of the stacked batteries in Examples 4 and 5 of the present invention are shown. Detailed Implementation

[0058] The present invention will be further described below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise stated, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0059] Example 1

[0060] A single-junction pin-structured perovskite solar cell includes, in sequence, a substrate, a hole transport layer, a passivated perovskite thin film layer, an electron transport layer, a hole blocking layer, and an electrode, such as... Figure 1 As shown.

[0061] The fabrication method of the above-mentioned single-junction pin structure perovskite solar cell is as follows:

[0062] S1. The ITO substrate was cleaned with deionized water, acetone and isopropanol in sequence. After drying with nitrogen, it was cleaned with ultraviolet-ozone for 20 minutes. Then, a Me-4PACz layer was prepared as a hole transport layer by spin coating with a concentration of 0.3 mg / ml ethanol solution at a rotation speed of 3000 rpm / s and annealed at 100°C for 10 minutes.

[0063] S2. Spin-coat a layer with a band gap of 1.54 eV, a concentration of 1.4 M, and a composition of Cs onto the prepared Me-4PACz hole transport layer. 0.03 (FA 0.97 MA 0.03 ) 0.97 Pb(I 0.97 Br 0.03 The perovskite solution was heated at 5000 rpm for 35 seconds, with ethyl acetate (EA) added dropwise as an antisolvent in the last 15 seconds. The solution was then annealed at 100°C for 30 minutes, resulting in a thickness of approximately 500 nm.

[0064] S3. Place the annealed perovskite film in a vacuum chamber, such as... Figure 2 As shown, a passivating agent, propylamine hydrochloride, is placed on the evaporation boat below it, and the evaporation rate is controlled by heating with a resistance wire. The coating pressure is 1*10 -3 Pa, the thickness of the thermally steamed perovskite-passivating agent intermediate is 10 nm, and then it is annealed at 100 °C for 5 minutes in an environment with 40% humidity to obtain the passivation layer;

[0065] S4. Preparation of a layer of fullerene (C) by thermal evaporation 60 As an electron transport layer, it is approximately 25 nm thick;

[0066] S5. A SnO2 layer with a thickness of approximately 20 nm was prepared using atomic layer deposition as a hole blocking layer.

[0067] S6. Using thermal evaporation in SnO x A layer of Ag is deposited as an electrode, with a thickness of approximately 100 nm, resulting in a device area of ​​approximately 0.0583 cm². 2 .

[0068] Example 2

[0069] One such Figure 3 The specific fabrication process of the vacuum evaporation vapor phase passivation pin-structured perovskite solar module cell shown is as follows:

[0070] S1. Use a laser scribing device to scribble the cleaned FTO conductive glass to separate the sub-cells, i.e., remove the FTO between the sub-cells. Then clean the scribed FTO conductive glass, spin coat it with 0.3 mg / mL Me-4PACz in a glove box at 3000 rpm, and finally place it on a hot plate to anneal at 100°C for 10 min.

[0071] S2. Spin-coat a layer with a band gap of 1.54 eV, a concentration of 1.4 M, and a composition of Cs onto the prepared Me-4PACz hole transport layer. 0.03 (FA 0.97 MA 0.03 ) 0.97 Pb(I 0.97 Br 0.03 The perovskite solution was heated at 5000 rpm for 35 seconds, with ethyl acetate (EA) added dropwise as an antisolvent in the last 15 seconds. The solution was then annealed at 100°C for 30 minutes, resulting in a thickness of approximately 500 nm.

[0072] S3. Place the annealed perovskite film in a vacuum chamber, such as... Figure 2 As shown, the aforementioned passivating agent, propylamine hydrochloride, is placed on the evaporation boat below it, and the evaporation rate is controlled by heating with a resistance wire. The coating pressure is 1*10 -3 Pa, the thickness of the thermally steamed perovskite-passivating agent intermediate is 3 nm, and then it is annealed at 100°C for 5 minutes in an environment with 40% humidity to obtain the passivation layer;

[0073] S4. Preparation of a layer of fullerene (C) by thermal evaporation 60 As an electron transport layer, it is approximately 25 nm thick;

[0074] S5. A SnO2 layer with a thickness of approximately 20 nm was prepared using atomic layer deposition as a hole blocking layer.

[0075] S6. Use a laser scribing device to scribing P2 60 micrometers behind P1, ensuring that the P2 line will not scratch the FTO.

[0076] S7. Move the device with P2 to a vacuum thermal evaporation instrument and use thermal evaporation to deposit a layer of Ag as an electrode with a thickness of about 100nm.

[0077] S8. Use a laser scribing device to scribble P3 60 micrometers behind P2, ensuring that the P3 line will not scratch the FTO.

[0078] S9. Using a high-energy laser, scribble P4 on the left rear ends of the device with P3 already scribed, and clear 5mm insulating boundaries on both sides to ensure that the metal electrodes of each cell are completely separated. This process fabricates a perovskite solar cell module with an aperture area of ​​21cm. 2 .

[0079] Example 3

[0080] One such Figure 4 The structure shown is used to fabricate a vacuum-deposited, vapor-passivated crystalline silicon / perovskite tandem solar cell. The specific fabrication process is as follows:

[0081] S1. The textured silicon battery was cleaned several times with isopropanol, dried with nitrogen, and then cleaned with ultraviolet-ozone for 20 minutes. Then, a Me-4PACz layer was prepared as a hole transport layer by spin coating with an ethanol solution of 0.3 mg / ml and a rotation speed of 3000 rpm / s. The mixture was then annealed at 100°C for 10 minutes.

[0082] S2. Co-evaporation of PbI2, CsBr, and PbCl2 inorganic precursor layers onto the prepared Me-4PACz hole transport layer at a rate ratio of 4:1:0.1, with a total thermal evaporation thickness of approximately 400 nm. Spin-coating of a 0.7 M organic solution (FAI, FABr, and MACl in a molar ratio of 6:1:1) in air with a humidity of 30-50% at a speed of 4000 rpm / s, followed by annealing at 150 °C for 30 minutes, with a thickness of approximately 650 nm.

[0083] S3. Place the annealed perovskite film in a vacuum chamber, such as... Figure 2 As shown, a passivating agent, propylamine hydrochloride, is placed on the evaporation boat below it, and the evaporation rate is controlled by heating with a resistance wire. The coating pressure is 1*10 -3 Pa, the thickness of the thermally steamed perovskite-passivating agent intermediate is 3 nm, and then it is annealed at 100°C for 5 minutes in an environment with 40% humidity to obtain the passivation layer;

[0084] S4. Preparation of a layer of fullerene (C) by thermal evaporation60 As an electron transport layer, it is approximately 15 nm thick;

[0085] S5. A SnO2 layer with a thickness of approximately 15 nm was prepared using atomic layer deposition as a hole blocking layer.

[0086] S6. Using magnetron sputtering on SnO x A layer of indium zinc oxide (IZO) is deposited on it, with a thickness of approximately 100 nm;

[0087] S7. Using thermal evaporation in SnO x A layer of Ag was deposited on it as an electrode, with a thickness of approximately 400 nm.

[0088] The device area is approximately 1.002 cm². 2 .

[0089] Example 4

[0090] A single-junction pin structure perovskite solar cell is prepared in a manner similar to that of Example 3, except that the annealing temperature in Example 3 is 120°C, the annealing humidity is 40%, and the annealing time is 10 minutes.

[0091] Example 5

[0092] A single-junction pin structure perovskite solar cell is prepared in a manner similar to that of Example 3, except that the annealing temperature in Example 3 is 80°C, the annealing humidity is 60%, and the annealing time is 1 minute.

[0093] Comparative Example 1

[0094] A perovskite solar cell is fabricated as follows:

[0095] S1. The ITO substrate was cleaned with deionized water, acetone and isopropanol in sequence. After drying with nitrogen, it was cleaned with ultraviolet-ozone for 20 minutes. Then, a Me-4PACz layer was prepared as a hole transport layer by spin coating with a concentration of 0.3 mg / ml ethanol solution at a rotation speed of 3000 rpm / s and annealed at 100°C for 10 minutes.

[0096] S2. Spin-coat a layer with a band gap of 1.54 eV, a concentration of 1.4 M, and a composition of Cs onto the prepared Me-4PACz hole transport layer. 0.03 (FA 0.97 MA 0.03 ) 0.97 Pb(I 0.97 Br 0.03A perovskite solution of 3 was prepared by annealing at 5000 rpm / s for 35 s. Ethyl acetate (EA) was added dropwise as an antisolvent in the last 15 s. The solution was then annealed at 100 °C for 30 minutes to obtain a perovskite film with a thickness of approximately 500 nm.

[0097] S3. Preparation of a layer of fullerene (C) by thermal evaporation 60 As an electron transport layer, it is approximately 25 nm thick;

[0098] S4. Prepare a layer of SnO using atomic layer deposition. x As a hole-blocking layer, its thickness is approximately 20 nm;

[0099] S5. Using thermal evaporation in SnO x A layer of Ag is deposited on it as an electrode, with a thickness of approximately 100 nm.

[0100] Comparative Example 2

[0101] The specific fabrication process of a perovskite solar module cell is as follows:

[0102] S1. Use a laser scribing device to scribble the cleaned FTO conductive glass to separate the sub-cells, i.e., remove the FTO between the sub-cells. Then clean the scribed FTO conductive glass, spin coat it with 0.3 mg / mL Me-4PACz in a glove box at 3000 rpm, and finally place it on a hot plate to anneal at 100°C for 10 min.

[0103] S2. Spin-coat a layer with a band gap of 1.54 eV, a concentration of 1.4 M, and a composition of Cs onto the prepared Me-4PACz hole transport layer. 0.03 (FA 0.97 MA 0.03 ) 0.97 Pb(I 0.97 Br 0.03 The perovskite solution was heated at 5000 rpm for 35 seconds, with ethyl acetate (EA) added dropwise as an antisolvent in the last 15 seconds. The solution was then annealed at 100°C for 30 minutes, resulting in a thickness of approximately 500 nm.

[0104] S3. Preparation of a layer of fullerene (C) by thermal evaporation 60 As an electron transport layer, it is approximately 25 nm thick;

[0105] S4. A SnO2 layer with a thickness of approximately 20 nm was prepared using atomic layer deposition as a hole blocking layer.

[0106] S5. Use a laser scribing device to scribing P2 60 micrometers behind P1, ensuring that the P2 line will not scratch the FTO.

[0107] S6. Move the device with P2 to a vacuum thermal evaporation instrument and use thermal evaporation to deposit a layer of Ag as an electrode with a thickness of about 100nm.

[0108] S7. Use a laser scribing device to scribble P3 60 micrometers behind P2, ensuring that the P3 line will not scratch the FTO.

[0109] S8. Using a high-energy laser, scribble P4 on the left and rear ends of the device with P3 already scribed, and clear 5mm insulating boundaries on both sides to ensure that the metal electrodes of each cell are completely separated. This process fabricates a perovskite solar cell module with an aperture area of ​​21cm. 2 .

[0110] Comparative Example 3

[0111] The specific fabrication process of a perovskite solar module cell is as follows:

[0112] S1. Use a laser scribing device to scribble the cleaned FTO conductive glass to separate the sub-cells, i.e., remove the FTO between the sub-cells. Then clean the scribed FTO conductive glass, spin coat it with 0.3 mg / mL Me-4PACz in a glove box at 3000 rpm, and finally place it on a hot plate to anneal at 100°C for 10 min.

[0113] S2. Spin-coat a layer with a band gap of 1.54 eV, a concentration of 1.4 M, and a composition of Cs onto the prepared Me-4PACz hole transport layer. 0.03 (FA 0.97 MA 0.03 ) 0.97 Pb(I 0.97 Br 0.03 The perovskite solution was heated at 5000 rpm for 35 seconds, with ethyl acetate (EA) added dropwise as an antisolvent in the last 15 seconds. The solution was then annealed at 100°C for 30 minutes, resulting in a thickness of approximately 500 nm.

[0114] S3. Place the annealed perovskite film on a spin coater and dynamically spin coat the isopropanol solution of the passivating agent with a concentration of 0.5 mg / ml at a speed of 5000 rpm / s for 35 s. Then anneal at 100°C for 5 minutes in an environment with 40% humidity.

[0115] S4. Preparation of a layer of fullerene (C) by thermal evaporation 60 As an electron transport layer, it is approximately 25 nm thick;

[0116] S5. Prepare a layer of SnO using atomic layer deposition. x As a hole-blocking layer, its thickness is approximately 20 nm;

[0117] S6. Use a laser scribing device to scribing P2 60 micrometers behind P1, ensuring that the P2 line will not scratch the FTO.

[0118] S7. Move the device with P2 to a vacuum thermal evaporation instrument and use thermal evaporation to deposit a layer of Ag as an electrode with a thickness of about 100nm.

[0119] S8. Use a laser scribing device to scribble P3 60 micrometers behind P2, ensuring that the P3 line will not scratch the FTO.

[0120] S9. Using a high-energy laser, scribble P4 on the left rear ends of the device with P3 already scribed, and clear 5mm insulating boundaries on both sides to ensure that the metal electrodes of each cell are completely separated. This process fabricates a perovskite solar cell module with an aperture area of ​​21cm. 2 .

[0121] Comparative Example 4

[0122] The specific fabrication process of a solar cell is as follows:

[0123] S1. The textured silicon battery was cleaned several times with isopropanol, dried with nitrogen, and then cleaned with ultraviolet-ozone for 20 minutes. Then, a Me-4PACz layer was prepared as a hole transport layer by spin coating with an ethanol solution of 0.3 mg / ml and a rotation speed of 3000 rpm / s. The mixture was then annealed at 100°C for 10 minutes.

[0124] S2 co-evaporated PbI2, CsBr, and PbCl2 inorganic precursor layers in the prepared Me-4PACz hole transport layer at a rate ratio of 4:1:0.1, with a total thermal evaporation thickness of approximately 400 nm. Then, a 0.7 M organic solution (FAI, FABr, and MACl in a molar ratio of 6:1:1) was spin-coated in air with a humidity of 30-50% at a speed of 4000 rpm / s. After that, it was annealed at 150 °C for 30 minutes, with a thickness of approximately 650 nm.

[0125] S3. Preparation of a layer of fullerene (C) by thermal evaporation 60 As an electron transport layer, it is approximately 15 nm thick;

[0126] S4. Prepare a layer of SnO using atomic layer deposition. x As a hole-blocking layer, its thickness is approximately 15nm;

[0127] S5, Using magnetron sputtering on SnO x A layer of indium zinc oxide (IZO) is deposited on it, with a thickness of approximately 100 nm;

[0128] S6. Using thermal evaporation in SnO xA layer of Ag was deposited on it as an electrode, with a thickness of approximately 400 nm.

[0129] Comparative Example 5

[0130] The specific fabrication process of a solar cell is as follows:

[0131] S1. The textured silicon battery was cleaned several times with isopropanol, dried with nitrogen, and then cleaned with ultraviolet-ozone for 20 minutes. Then, a Me-4PACz layer was prepared as a hole transport layer by spin coating with an ethanol solution of 0.3 mg / ml and a rotation speed of 3000 rpm / s. The mixture was then annealed at 100°C for 10 minutes.

[0132] S2 co-evaporated PbI2, CsBr, and PbCl2 inorganic precursor layers in the prepared Me-4PACz hole transport layer at a rate ratio of 4:1:0.1, with a total thermal evaporation thickness of approximately 400 nm. Then, a 0.7 M organic solution (FAI, FABr, and MACl in a molar ratio of 6:1:1) was spin-coated in air with a humidity of 30-50% at a speed of 4000 rpm / s. After that, it was annealed at 150 °C for 30 minutes, with a thickness of approximately 650 nm.

[0133] S3. Place the annealed perovskite film on a spin coater and dynamically spin coat the isopropanol solution of the passivating agent with a concentration of 0.5 mg / ml at a speed of 5000 rpm / s for 35 s. Then anneal at 100°C for 5 minutes in an environment with 40% humidity.

[0134] S4. Preparation of a layer of fullerene (C) by thermal evaporation 60 As an electron transport layer, it is approximately 15 nm thick;

[0135] S5. Prepare a layer of SnO using atomic layer deposition. x As a hole-blocking layer, its thickness is approximately 15nm;

[0136] S6. Using magnetron sputtering on SnO x A layer of indium zinc oxide (IZO) is deposited on it, with a thickness of approximately 100 nm;

[0137] S7. Using thermal evaporation in SnO x A layer of Ag, approximately 400 nm thick, is deposited as an electrode. The device area is approximately 1.002 cm². 2 .

[0138] Comparative Example 6

[0139] The specific fabrication process of a solar cell is as follows:

[0140] S1. The ITO substrate was cleaned with deionized water, acetone and isopropanol in sequence. After drying with nitrogen, it was cleaned with ultraviolet-ozone for 20 minutes. Then, a Me-4PACz layer was prepared as a hole transport layer by spin coating with a concentration of 0.3 mg / ml ethanol solution at a rotation speed of 3000 rpm / s and annealed at 100°C for 10 minutes.

[0141] S2. Spin-coat a layer with a band gap of 1.54 eV, a concentration of 1.4 M, and a composition of Cs onto the prepared Me-4PACz hole transport layer. 0.03 (FA 0.97 MA 0.03 ) 0.97 Pb(I 0.97 Br 0.03 The perovskite solution was heated at 5000 rpm for 35 seconds, with ethyl acetate (EA) added dropwise as an antisolvent in the last 15 seconds. The solution was then annealed at 100°C for 30 minutes, resulting in a thickness of approximately 500 nm.

[0142] S3. Place the annealed perovskite film in a vacuum chamber, such as... Figure 2 As shown, the aforementioned passivating agent is placed on the evaporation boat below it, and the evaporation rate is controlled by heating with a resistance wire. The coating pressure is 1*10 -3 Pa, the thermal evaporation thickness is 10 nm, and no annealing operation is performed;

[0143] S4. Preparation of a layer of fullerene (C) by thermal evaporation 60 As an electron transport layer, it is approximately 25 nm thick;

[0144] S5. Prepare a layer of SnO using atomic layer deposition. x As a hole-blocking layer, its thickness is approximately 20 nm;

[0145] S6. Using thermal evaporation in SnO x A layer of Ag is deposited as an electrode, with a thickness of approximately 100 nm, resulting in a device area of ​​approximately 0.0583 cm². 2 .

[0146] Result detection

[0147] The photovoltaic performance of the perovskite solar cells in the examples and comparative examples was tested, and the specific methods are as follows:

[0148] Current-voltage curves were measured using a Keithley 2400 at AM 1.5G, with the spectral intensity adjusted to 100 mW cm⁻¹ using a standard silicon cell with appropriate filters. -2 .

[0149] The device results of Example 1 are shown in Table 1 and the results of Comparative Examples 1 and 6. Figure 5 As shown, under sunlight conditions, the open-circuit voltage and fill factor of Example 1 are significantly higher than those of the control group.

[0150] Table 1

[0151]

[0152] In addition, XRD analysis was performed on the perovskite solar cells of the examples and comparative examples. The X-ray diffraction patterns of Example 1, Comparative Examples 1 and 6 are shown below. Figure 10 As shown, after vapor phase passivation, the diffraction peak intensity of the perovskite film increases and the lead iodide content decreases, but impurity phases also appear, which is detrimental to the improvement of device efficiency. After annealing, the diffraction peak intensity of the perovskite film increases significantly, the lead iodide content decreases, and the diffraction peaks of the impurity phases disappear, indicating that the crystal quality of the perovskite film is further improved, which corresponds to the device efficiency.

[0153] The device results of Example 2 and the results of Comparative Examples 2 and 3 are shown in Table 2 and 3. Figure 6 As shown, under sunlight conditions, the open-circuit voltage and fill factor of Example 2 are significantly higher than those of Comparative Example 2. In addition, the passivation effect of Example 2 is better than that of Comparative Example 3, which is based on solution spin coating, indicating that the vapor phase passivation method is more suitable for large-area perovskite solar cells and modules.

[0154] Table 2

[0155]

[0156] The device results of Example 3 and the results of Comparative Examples 4 and 5 are shown in Table 3 and... Figure 7 As shown, under sunlight conditions, the open-circuit voltage and fill factor of Example 3 are significantly higher than those of Comparative Example 4. Furthermore, the passivation effect of Example 3 is superior to that of Comparative Example 5, which is passivated using a solution spin-coating method, indicating that the vapor-phase passivation method is more suitable for textured silicon-perovskite solar cells. The cross-sectional SEM image of the cell in Example 3 is shown below. Figure 8 As shown in the figure, the cross-sectional SEM of the battery in Comparative Example 4 is as follows. Figure 9 As shown, after vapor phase passivation, the grain morphology of the perovskite film was improved and the porosity was reduced.

[0157] Table 3

[0158]

[0159] The device results for Examples 4 and 5 are shown in Table 4 and 5. Figure 11As shown, under sunlight conditions, the efficiencies of Examples 4 and 5 are higher than those of Comparative Example 4, but lower than those of Example 3, indicating that the vapor-phase passivating agent has a certain effect on perovskite thin films, but the subsequent annealing conditions are equally important. Optimized annealing conditions can further improve the performance of photovoltaic devices.

[0160] Table 4

[0161]

[0162] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A method for vapor-phase passivation of perovskite thin films, characterized in that, Includes the following steps: A perovskite-passivating agent intermediate is formed on the surface of a perovskite film by vacuum evaporation. The perovskite film intermediate is then annealed to form a passivation layer, resulting in a passivated perovskite film. The annealing temperature is 80℃~120℃, the humidity is 20%~60%, and the annealing time is 1~10 minutes.

2. The perovskite thin film vapor phase passivation method as described in claim 1, characterized in that, The thickness of the perovskite-passivating agent intermediate is 0.1–20 nm.

3. The perovskite thin film vapor phase passivation method as described in claim 1, characterized in that, The vacuum evaporation rate is / s, the gas pressure in the chamber during vapor deposition is 1*10 -2 ~1*10 -4 Pa.

4. The perovskite thin film vapor phase passivation method as described in claim 1, characterized in that, The annealing process is carried out at a temperature of 100°C, a humidity of 30%–40%, and a annealing time of 5 minutes.

5. The perovskite thin film vapor phase passivation method as described in claim 1, characterized in that, The passivating agent is a small molecule organic halide salt AX.

6. The perovskite thin film vapor phase passivation method as described in claim 5, characterized in that, The small molecule organic halide AX contains A. + X is any one of the following: methylamine, ethylamine, propylamine, pentylamine, benzylamine, and phenethylamine ion. - It is any one or more of the following: chloride ion, bromide ion, iodide ion, cyanate ion, thiocyanate ion, trifluoroacetate ion, hexafluorophosphate ion, methanesulfonate ion, tetrafluoroborate ion, acetate ion, and formate ion.

7. A solar cell, comprising, in sequence, a substrate, a hole transport layer, a passivated perovskite thin film layer, an electron transport layer, a hole blocking layer, and an electrode, characterized in that, The passivated perovskite thin film layer is prepared by the perovskite thin film vapor phase passivation method according to any one of claims 1 to 6.

8. The solar cell as described in claim 7, characterized in that, The solar cell is any one of textured silicon-perovskite tandem solar cell, large-area perovskite solar cell, or small-area single-junction perovskite solar cell.

9. A method for fabricating a perovskite solar cell, characterized in that, Includes the following steps: S1. Prepare a hole transport layer on a substrate; S2. Prepare a perovskite thin film on the hole transport layer obtained in step S1; S3. A passivated perovskite thin film layer is prepared by the method described in any one of claims 1 to 6; S4. An electron transport layer is prepared on the layer obtained in step S3; S5. A hole-blocking layer is prepared on the layer obtained in step S4. S6. Prepare a back electrode on the layer obtained in step S5.

10. The method for preparing a perovskite solar cell as described in claim 9, characterized in that, The perovskite thin film is prepared by one or more of the following methods: solution spin coating, solution blade coating, solution slot coating, solution spraying, solution inkjet printing, vacuum evaporation, laser ablation, and magnetron sputtering.